(untitled) (Revista de História da UEG (REVHIST), 2021)
This article examines the attempts of the groups linked to right wing parties - especially the majority sectors of the National Party - in collusion with the conservative wing of the Catholic Church to install a private and Catholic university. The regional and global context favorable to the privatization and differentiation of the higher education system, as well as the change in the national political situation after the rise of the National Party to the government, after almost one hundred years of predominance of the traditional rival party -Partido Colorado-, generated conditions conducive to the advancement of these proposals. The work analyzes the debates, positions and alliances of the various actors involved, and attempts to account for the convergence of sectoral, political-ideological, corporate interests of different origins. Keywords: right wings. Universities. History.